Inexplicável silêncio ante a situação do cônjuge inocente - Giraldo, José Silvio Botero (Revista eclesiástica brasileira, 2014)
Regarding the issue of the “innocent spouse abandoned”, we notice there is an inexplicable silence either on the part of the Church’s Magisterium or on the part of theologians and scholars. During the sessions of the Second Vatican Council and the Synod of Bishops on the Family (1980), there have been some suggestions that we should deal with this question. The Council of Trent condemned as “anathema” those who denied that adultery dissolves the marriage bond, even in the case of an innocent spouse. Notwithstanding the limits that this “anathema” holds, it seems that the doctrine of the Church became stratified. Today, theological reflection points to perspectives that allow us to meet this problem in terms of a pastoral solution.